Ceramic sealing parts and manufacturing method thereof
Patent Information
- Application Number
- JP2023196866
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-11-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-11-20
Smart Images

Figure 0007635345000001_ABST
Abstract
Description
[Technical field]
[0001] The embodiment is roughly , Sera Ceramic sealed parts made by joining mixed parts and metal parts (hereinafter referred to as "ceramic sealed parts"); and The present invention relates to a manufacturing method thereof. [Background technology]
[0002] As ceramic sealing parts for magnetrons, power tubes, and electronic tubes, ceramic sealing parts are used in which a metallized layer mainly made of a high melting point metal such as molybdenum (Mo) is formed on a ceramic part such as alumina (aluminum oxide: Al2O3). Ceramic sealing parts can protect the inside from the external environment and provide electrical insulation by bonding ceramics and metal to block outside air and hermetically seal the inside of the part. For example, a ceramic sealing part as shown in Figure 1 has a metallized layer mainly made of molybdenum formed on the ring parts on the upper and lower end surfaces of a cylindrical ceramic part made of alumina sintered body. A nickel (Ni) layer of a certain thickness is formed on the surface of this metallized layer to improve the bonding strength with other metal parts and to perform sealing. This nickel part and the cylindrical metal part are bonded with silver solder (e.g. BAg-8).
[0003] As a ceramic sealed part, an electron tube having a vacuum airtight structure in which a metal surface made of molybdenum is formed on a ceramic cylinder and an iron metal cylinder is joined with a brazing material has been disclosed (Patent Document 1). According to Patent Document 1, a low-cost electron tube can be manufactured by replacing the metal cylinder with iron from Kovar.
[0004] Also, a vacuum switch outer tube has been disclosed in which a nickel-based alloy is bonded to ceramics by an active metal, without using high-melting-point metals such as molybdenum (Patent Document 2). According to Patent Document 2, it is possible to manufacture a vacuum switch outer tube with high bonding strength without producing intermetallic compounds that cause an unstable bond. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Application No. 1-46978 [Patent Document 2] JP 2001-220253 A Summary of the Invention [Problem to be solved by the invention]
[0006] The ceramics used in ceramic sealing parts are hard but brittle. One of the causes of this brittleness is the influence of the surface condition. If there are scratches or other defects on the surface of the ceramic, these defects can become the starting point of fracture. For this reason, polishing the surface of the ceramic to remove the defects and reduce the surface roughness improves the mechanical reliability of the ceramic. For example, ceramic balls for bearings have mechanical properties that enable them to withstand high speeds and rotations by reducing the surface roughness through polishing.
[0007] However, when metallizing the surface of ceramics to join them to metals, the strength of the joint (metallization) is greater when the ceramic surface is moderately rough. This is because a rough surface allows a larger area to be joined through chemical reactions, and the metallization components penetrate into the recesses, physically increasing the mechanical strength through an anchor effect. For this reason, there is a trade-off between the surface condition of ceramics, where a smaller surface roughness is better to increase the strength of the ceramic, and a larger surface roughness is better to increase the joining strength.
[0008] On the other hand, a strong bonding layer is required to ensure sealing (airtightness) when bonding ceramics and metals. However, the thermal expansion coefficients of ceramics and metals are different (for example, the thermal expansion coefficient of alumina is 7.2×10 -6 / ℃, copper 16.5×10 -6 / ℃, carbon steel 11.7×10 -6 / ℃), the difference in thermal expansion generates stress, which can easily lead to cracks. When joining the same type of metal, there is no difference in the joining, but when joining multiple types of metal with different properties, differences in the joining are likely to occur, which can impair the sealing ability.
[0009] Also, to increase the bonding strength between ceramics and metals without changing the state of the ceramics, there is a method of increasing the amount of components that contribute to bonding during metallization and raising the bonding temperature, for example. However, when increasing the bonding strength of one of multiple metals with different properties, it is necessary to use two types of paste and two different bonding temperatures, which makes the manufacturing process complicated. the law of nature Poor cost performance. Also, when increasing the joint strength of the joint between both metals, the joining temperature also rises for metals that do not require high joint strength, which causes a further difference in thermal expansion and may impair sealing.
[0010] The embodiments are intended to solve such problems, and relate to a highly productive ceramic sealed part and a manufacturing method thereof that suppresses poor joining and leak defects when a ceramic part is joined to a plurality of metal parts with different characteristics. [Means for solving the problem]
[0011] Ceramics according to the embodiment Sealing Parts are: Ceramic parts Ceramic seal with two different metal parts bonded to the end surface Product can be, The ceramic parts When the arithmetic mean surface height of one end face is S1 and the arithmetic mean surface height of the other end face is S2, S1 / S2 is 1.2 or more. In addition, a metal part made of iron, an iron alloy, or an iron-nickel alloy is joined via a joining layer to the end face having the arithmetic mean surface height S1. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a perspective view showing an example of a ceramic sealing component according to an embodiment; [Diagram 2] FIG. 1 is a cross-sectional view showing an example of a ceramic part according to an embodiment. [Diagram 3] FIG. 1 is a cross-sectional view showing an example of a ceramic sealing component according to an embodiment. [Figure 4] 1 is a cross-sectional view showing an example of a manufacturing process for a ceramic sealed component according to an embodiment; [Diagram 5] 1 is a cross-sectional view showing an example of a manufacturing process for a ceramic sealed component according to an embodiment; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Ceramics according to the embodiment Sealing Parts are: Ceramic parts 2 on the end face Different Ceramic seals bonded to metal parts Product can be, The ceramic parts When the arithmetic mean surface height of one end face is S1 and the arithmetic mean surface height of the other end face is S2, S1 / S2 is 1.2 or more. In addition, a metal part made of iron, an iron alloy, or an iron-nickel alloy is joined via a joining layer to the end face having the arithmetic mean surface height S1.
[0014] FIG. 1 shows a perspective view of an example of a ceramic sealing part 1 according to an embodiment. Reference numeral 2 denotes a cylindrical ceramic part, and reference numerals 3 and 4 denote cylindrical metal parts made of different materials. The metal parts 3 and 4 are joined at the end faces of the ceramic part 2. FIG. 1 shows an example in which the metal part 3 is joined to the upper end face of the ceramic part 2, and the metal part 4 is joined to the lower (opposite) end face. The embodiment is not limited to this shape, and may be a ceramic part or metal part in a rectangular tube shape, or may be a form in which the lower bottom face is a ceramic part and only the upper side (one side) is joined to a metal part, or a form in which two metal parts are joined to one side. part It is permitted to join metal parts to ceramic parts having the above openings.
[0015] An example of a cross-sectional view of a ceramic part according to an embodiment is shown in Fig. 2. The upper (one side) end face of the cylindrical ceramic part 2 is designated as 21, and the lower (opposite side) end face is designated as 22. When the arithmetic mean surface height of end face 21 is designated as S1, and the arithmetic mean surface height of end face 22 is designated as S2, S1 / S2 ≧ 1.2. Note that in Fig. 2 and subsequent figures, end face 21 is shown in a black layer to distinguish it from end face 22.
[0016] FIG. 3 shows a cross-sectional view of a ceramic sealing part 1 according to an embodiment. 3 is a metal A part (hereinafter, abbreviated as "metal A part") made of metal A, and 4 is a metal B part (hereinafter, abbreviated as "metal B part") made of metal B. At this time, the metal A part 3 and the metal B part 4 are made of different materials. For example, the metal A part 3 is a cylindrical metal part made of stainless steel, and the metal B part 4 is a cylindrical metal part made of copper (Cu). At this time, the metal A part 3 is joined via a joining layer 5 to an end face 21 having an arithmetic mean surface height S1. Also, the metal B part 4 is joined via a joining layer 5 to an end face 22 having an arithmetic mean surface height S2. For example, the ceramic part 2 is a cylindrical ceramic part made of aluminum oxide (alumina), and the joining layer 5 is configured to be joined by an active metal brazing material layer.
[0017] The ceramic part 2 is preferably one of alumina, zirconia-added alumina (Alzir), silicon nitride, and aluminum nitride. Alumina includes alumina-based ceramics in which other ceramics are added to alumina. For example, zirconia-added alumina is a sintered body in which alumina and zirconium oxide are mixed. A sintering aid other than zirconia may be added to the alumina. This is because the added sintering aid forms a grain boundary phase consisting of a glass phase to densify the alumina sintered body. Examples of the sintering aid include compounds of manganese (Mn), silicon (Si), magnesium (Mg), calcium (Ca), and the like. It is preferable to add at least one of these sintering aids, Mn, Si, Mg, and Ca, in a total amount of 1 to 15 mass% in terms of oxide. In addition, a sintering aid may be added to silicon nitride and aluminum nitride to densify them. Examples of the sintering aid include oxides of rare earth elements, Mg, Ca, aluminum (Al), titanium (Ti), hafnium (Hf), and the like. It is preferable to add at least one of these in an amount of 1 to 15 mass % calculated as oxide.Of these ceramic parts, alumina is excellent in cost performance.
[0018] The ceramic part 2 has two end faces to which the metal part is joined. When one end face of the ceramic part 2 is designated as 21, the other end face is designated as 22. When the arithmetic mean surface height of the end face 21 is designated as S1 and the arithmetic mean surface height of the end face 22 is designated as S2, S1 / S2 ≧ 1.2. To adjust the surface roughness of the ceramic part 2 to the range of S1 / S2 ≧ 1.2, there are a method of adjusting it in a process before sintering and a method of adjusting it in a process after sintering. For example, a method of adjusting it in a process before sintering includes a method of mechanically roughening or mechanically finely roughening one end face of a molded body molded by pressing. To roughen the surface roughness of a molded body, the surface is polished with a coarse buff or a material with a surface equivalent to that of a buff (such as resin or ceramics). To fine it, it is possible to adjust it by polishing the surface with a fine buff or a material with a surface equivalent to that of a buff. In addition, in the production line, it is possible to roughen the surface of the end face of the molded article on the side where it is placed by placing the molded article on a setter with a rough surface and applying vibration to it.
[0019] As for the method of adjusting the surface roughness in the process after sintering, in addition to the above-mentioned buffing, honing (blasting) treatment can be used to change the surface roughness by rough honing or fine honing. Surface roughness can also be adjusted by polishing with grindstones of different roughness.
[0020] The surface roughness is the arithmetic mean height (Sa) of the surface. The arithmetic mean height of the surface is measured in accordance with "Geometric Characteristics Specifications (GPS) - Surface Texture: Three-Dimensional - Part 6: Classification of Surface Texture Measurement Methods (JIS B0681-6:2014)". The measurement location and area are measured at approximately the center of the end face part, which is the joint part, with the distance of 1 / 2 the width of the end face as the diameter. For example, when joining the entire cylindrical end face part, if the width of the end face (difference between the outer diameter and the inner diameter) is 10 mm, the diameter is measured at 5 mm. Also, if there is a chamfer, it is 1 / 2 the width excluding the chamfered part. In this case, if the width to be measured is not uniform, the largest (widest) point is measured. Also, if the maximum width of the two end faces is different, it is adjusted to the diameter of the measurement area of the smaller end face. Measurements can be performed using a non-contact surface roughness meter and a laser microscope (such as Keyence's VK-X series).
[0021] The material of the metal A part 3 to be joined to the end surface 21 of the ceramic part 2 is preferably iron (Fe), iron alloy, or iron-nickel alloy (hereinafter, abbreviated as "iron, iron alloy, etc."). The iron alloy is an alloy steel such as carbon steel, such as rolled steel, chromium steel, or stainless steel. The iron-nickel alloy includes 42 alloy (Ni 42 mass%, Mn 0.8 mass% or less, balance Fe) and Kovar (Ni 29 mass%, Co 17 mass%, balance Fe). Iron and iron alloys are excellent in cost performance, while iron-nickel alloys are excellent in physical properties such as thermal expansion coefficient. In addition, iron, iron alloys, and iron-nickel alloys are preferably plated to improve wettability during joining and to prevent rust. Nickel plating is preferable as the plating. This is because nickel plating has excellent heat resistance and prevents diffusion of molecules between the plating and the material.
[0022] The material of the metal B part 4 to be joined to the end surface 22 of the ceramic part 2 is preferably copper or a copper alloy. The copper alloy is pure copper such as oxygen-free copper, tough pitch copper, deoxidized copper, or a high-copper alloy such as beryllium copper or titanium copper. The metal part is manufactured by processing into a predetermined shape by pressing, cutting, bending, or the like.
[0023] The ceramic part 2 and the metal part are joined by a joining layer 5. Typical methods for forming a joining layer include the active metal method and the high melting point metal method. The active metal method uses an active metal such as titanium (Ti). Examples of active metals other than titanium include zirconium (Zr) and hafnium (Hf). An example of an active metal brazing material is a mixture of titanium and copper (Cu). For example, titanium is 0.1 to 10 mass%, and copper is the balance. Another example of an active metal brazing material is a mixture of titanium, silver, and copper. Titanium is 0.1 to 10 mass%, copper is 10 to 60 mass%, and silver is the balance. In order to control the diffusion of the active metal brazing material during joining, 1 to 15 mass% of one or more selected from indium (In), tin (Sn), aluminum (Al), silicon (Si), carbon (C), and magnesium (Mg) may be added as necessary. The active metal brazing material paste is printed on the surface of the ceramic part and then dried. Thereafter, a metal part is placed in contact with the surface of the printed and dried paste, and the ceramic part and the metal part are joined by heating at 780 to 820°C in a vacuum or in a non-oxidizing gas.
[0024] The high melting point metal method is a method in which a paste made of powder of a high melting point metal such as molybdenum (Mo) or tungsten (W) is printed on the surface of the ceramic and heated at high temperature. A typical high melting point metal method is the molybdenum-manganese (Mn) method. In the molybdenum-manganese method, for example, 5 to 15 mass% of manganese powder is added to molybdenum powder to make a paste. The high melting point metal paste is printed on the surface of the ceramic part and then dried. Then, it is heated at 1400 to 1500 °C in a wet hydrogen nitrogen atmosphere gas to form a metallized layer of a high melting point metal on the surface of the ceramic part. Since the layer of the high melting point metal formed on the surface of the ceramic has poor wettability, plating with nickel (Ni) or the like is performed. A silver brazing foil or the like is placed between the nickel plating and the metal part and heated to 780 to 820 °C to perform brazing and joining.
[0025] Both active metal joining and brazing joining after high melting point metal are heated to a joining temperature of approximately 800°C. Due to the thermal expansion coefficient and elongation (hardness) of the metal parts, there will be differences in the joining state between metal A part 3, which is iron or iron alloy, and metal B part 4, which is copper or copper alloy. The thermal expansion coefficients of iron and iron alloys, and copper and copper alloys, are greater than that of ceramics. Both expand when heated and contract when cooled after joining with the ceramic. At this time, due to the difference in the thermal expansion coefficients of the metal and ceramics, the metal part contracts more than the ceramic part, generating stress. For example, the thermal expansion coefficient of SUS304, an austenitic stainless steel, is 17.3 x 10 ―6 / °C, and the thermal expansion coefficient of copper is 17.7 x 10 ―6 / ℃. However, the Vickers hardness of SUS304 is 150, which is harder than that of copper (50). For this reason, SUS304 is less likely to deform when cooled than copper. Thus, when it comes to bonding to ceramics, stress is more likely to occur in iron and iron alloys than in copper and copper alloys. For this reason, even if no fracture occurs when bonding ceramics to copper or copper alloys, fracture may occur when bonding to iron and iron alloys.
[0026] In order to increase the bonding strength on the side where the stress is large, the proportion of reactive components in the paste can be increased, the bonding temperature can be raised, etc., but this also increases damage to the entire part, including the side where the stress is not applied. In contrast, the ceramic part according to the embodiment has a large surface roughness on the surface that is bonded to the metal that is easily broken by the stress. This makes it relatively easy to manufacture a ceramic part that can be bonded to two or more types of metal parts.
[0027] The bonding strength of the bonding layer formed by the active metal method and the refractory metal method is greater when the surface roughness of the ceramic part is greater. This is because the reaction area becomes larger as the surface roughness increases. Also, the bonding layer penetrates into the ceramic part, and the anchor effect increases the physical bonding strength.
[0028] The above-mentioned examples are of copper and copper alloys and iron and iron alloys, but combinations with metals having other linear expansion coefficients and hardness are also possible. Furthermore, even if the metals are the same, it is possible to apply the combination of shapes that are easy to deform and shapes that are difficult to deform. For example, even if the metal parts are the same type of cylindrical shape, if they are thin, they are easy to deform, and if they are thick, they are difficult to deform.
[0029] FIG. 4 shows a process diagram (cross-sectional view) of a method for manufacturing a ceramic sealed component using an active metal method according to an embodiment. The method for manufacturing a ceramic sealed component according to an embodiment is a method for manufacturing a ceramic sealed component having two metal components made of different materials bonded to its end faces. First, a ceramic component is prepared in which the arithmetic mean surface height of one end face is S1 and the arithmetic mean surface height of the other end face is S2, such that S1 / S2≧1.2. Next, the ceramic component and the metal component are bonded to each other using one or more active metals selected from titanium, zirconium, and hafnium, and one or more brazing metals selected from copper and silver.
[0030] FIG. 4(a) is a cross-sectional view of a ceramic part 2. When the arithmetic mean surface height S21 of the end face 21 and the arithmetic mean surface height S22 of the end face 22 are taken as the values, S21 / S22≧1.2. FIG. 4(b) shows a state in which an active metal brazing paste is printed and dried on the ceramic part 2, and then heated in a vacuum or in a non-oxidizing gas to form an active metal brazing layer 6. The surface of the active metal brazing layer 6 before bonding is substantially flat, since the paste is printed on the flat end face of the ceramic part. In FIG. 4(b), the active metal brazing paste is printed only on the flat part of the end, but it is also possible to form a chamfer and print the active metal brazing material. FIG. 5(c) shows a state in which the metal parts are bonded by placing the metal parts on the surface of the active metal brazing layer and heating them. Although it is possible to bond multiple metal parts separately, it is preferable to place and bond them at the same time, since stress is generated again by the metal parts that were previously bonded. It is also possible to join ceramic and metal parts by placing the metal parts on the surface of the printed and dried active metal brazing material and then heating it, rather than first heating the active metal brazing material layer and then placing the metal parts on it and heating it.
[0031] FIG. 5 shows a process diagram (cross-sectional view) of a method for manufacturing a ceramic sealed component using a high melting point metal method according to an embodiment. The method for manufacturing a ceramic sealed component according to an embodiment is a method for manufacturing a ceramic sealed component having two metal components made of different materials bonded to its end faces. First, a ceramic component is prepared in which S1 / S2≧1.2, where S1 is the arithmetic mean surface height of one end face and S2 is the arithmetic mean surface height of the other end face. Next, a metallized layer made of a high melting point metal is formed on the end face of the ceramic component. Next, nickel plating is formed on the surface of the metallized layer. Next, the nickel plating and the metal component are bonded with a brazing material containing copper and silver.
[0032] FIG. 5(a) is a cross-sectional view of a ceramic part 2. When the arithmetic mean surface height S21 of the end face 21 and the arithmetic mean surface height S22 of the end face 22 are both defined as S21 / S22≧1.2. In FIG. 5(b), a metallized layer 7 is formed on both end faces of the ceramic part 2. The metallized layer 7 is formed by printing and drying a high melting point metal paste and heating it at a high temperature. FIG. 5(c) shows a state in which a plating layer 8 is formed on the surface of the metallized layer. The plating layer is formed by electroplating or electroless plating. FIG. 5(d) shows a state in which a brazing material layer 9 is formed between the plating layer and the metal part, and the ceramic part 2 and the metal part are joined. The brazing material layer is formed by placing a brazing material sheet or the like between the metal part and the plating surface and heating it.
[0033] In the manufacturing method of a ceramic sealed component according to the embodiment, a metal component such as iron or an iron alloy is joined via a joining layer to an end face of a ceramic component having an arithmetic mean surface height S1, and a metal component such as copper or a copper alloy is joined via a joining layer to an end face of a ceramic component having an arithmetic mean surface height S2.
[0034] Next, a method for manufacturing the ceramic parts and ceramic sealed parts according to the embodiment will be described. As long as the ceramic parts and ceramic sealed parts have the above-mentioned configuration, the manufacturing method is not particularly limited, but the following method can be mentioned as a method for obtaining the ceramic parts and ceramic sealed parts with a good yield.
[0035] An example of the ceramic part according to the embodiment is cylindrical, for example, with an outer diameter of 50 mm, an inner diameter of 38 mm, and a height of 50 mm. Ceramic parts are prone to chipping and cracking at their corners due to external impacts. For this reason, it is preferable to chamfer the outer and inner peripheries of the end faces. The chamfer shape may be C-chamfer or R-chamfer, and the chamfer size is preferably 0.1 to 2 mm.
[0036] The materials of the metal parts according to the embodiment include iron and iron alloys, copper and copper alloys, iron-nickel alloys such as 42 alloy and Kovar, tungsten, molybdenum, etc. Iron and iron alloys are excellent in cost performance, while copper and copper alloys are easily deformed to relieve stress caused by the difference in thermal expansion. For this reason, it is preferable to form metal parts from iron and iron alloys, or copper and copper alloys.
[0037] An example of the shape of the metal part is a substantially cylindrical shape. The joining end of the metal part may be straight so that it is joined vertically to the ceramic end face, or it may be bent at a substantially right angle inward or outward so that it is joined horizontally to the ceramic end face. For example, the height is 20 mm, and in the straight shape, the outer diameter is 46 mm and the inner diameter is 44 mm, while in the bent shape, the outer diameter is 48 mm, the inner diameter is 46 mm, and the inner diameter of the bent end is 40 mm. The joining with the straight metal part is an edge seal, and the joining is made by a line, so stress is not easily applied. The joining with the bent metal part is a butt seal, and the joining is made by a surface, so leak failure is not easily caused. These metal parts can be plated with nickel or the like to improve corrosion resistance and wettability.
[0038] The form of the parts to be joined by the active metal brazing material is preferably a paste. The active metal brazing material paste is prepared by adding an organic binder and an organic solvent to a mixture of active metal powder and brazing metal powder. The organic binder is not particularly limited as long as it is burned away during the drying process or the joining (heating) process. A preferred example is ethyl cellulose. The organic solvent is not particularly limited as long as it is burned away during the drying process or the firing process. A preferred example is terpineol or butyl carbitol. The active metal brazing material paste is prepared by crushing and mixing the active metal powder and the brazing metal powder, and then mixing them with the organic binder and the organic solvent. The ratio of the active metal contained in the active metal brazing material component is 0.1 to 15 mass%, preferably 0.5 to 10 mass%.
[0039] The printing thickness of the active metal brazing paste is 2 A thickness of 0 to 150 μm is preferable. If the printing thickness is less than 20 μm, the thickness of the active metal brazing material layer varies, lowering the joining strength. On the other hand, if it exceeds 150 μm, no further effect can be obtained. The paste is printed in a uniform thickness on the end surface of the ceramic component by screen printing or the like. If the printing thickness is not uniform, the active metal brazing material will be excessive in the thick parts, causing brazing material to accumulate and cracks due to thermal stress. In addition, in the thin parts, leakage defects will occur due to the breakage of the active metal brazing material. For this reason, it is preferable that the difference in printing thickness between the thick and thin parts is 15 μm or less, and more preferably 10 μm or less.
[0040] The paste printed on the ceramic parts is dried in the air or the like. If the drying temperature is low and the drying time is short, the solution components of the paste are not sufficiently volatilized, and voids may occur during bonding. Conversely, if the drying temperature is high and the drying time is long, oxidation of the paste surface may progress, and the bonding temperature may change. For this reason, the drying temperature is 50 to 100°C, preferably 60 to 80°C. The drying time is 5 to 30 minutes, preferably 10 to 20 minutes.
[0041] After the paste is dried, the metal parts are placed on the dried paste surface and heated to bond them. The bonding temperature is 600 to 850°C, preferably 700 to 800°C. The bonding time is preferably in the range of 5 to 60 minutes after the bonding temperature is reached. If the bonding temperature is low and the bonding time is short, the active metal brazing material may not melt sufficiently and bonding may not occur. Conversely, if the bonding temperature is high and the bonding time is long, the active metal brazing material may melt too much and spread, causing voids or brazing breaks. The active metal bonding atmosphere may be in a vacuum or a non-oxidizing atmosphere as necessary. When performing in a vacuum, a 1×10 -2 The pressure is preferably 100 Pa or less. Examples of the non-oxidizing atmosphere include a nitrogen atmosphere and an argon atmosphere. By using a vacuum or a non-oxidizing atmosphere, the active metal brazing material layer can be prevented from being oxidized. This improves the joining strength. A continuous furnace or a batch furnace is used for brazing. A continuous furnace is superior in terms of mass production, and it is easy to control the temperature and atmosphere. stomach The furnace is a batch furnace. The active brazing metal layer is formed by heating in the above atmosphere for a predetermined period of time.
[0042] On the other hand, the form of the metallized parts using high melting point metals is a paste. The high melting point metal paste is a mixture of high melting point metal powder such as molybdenum or tungsten and additive powder, to which an organic binder and an organic solvent are added. For example, a molybdenum-manganese paste is a mixture of molybdenum powder and 10 mass% manganese powder. The organic binder is not particularly limited as long as it is burned away during the drying process or the joining (heating) process. A preferred example is ethyl cellulose. The organic solvent is not particularly limited as long as it is burned away during the drying process or the firing process. A preferred example is terpineol or butyl carbitol. The high melting point metal paste is prepared by crushing and mixing a high melting point metal powder and an additive powder, and then mixing the mixture with an organic binder and an organic solvent.
[0043] The printing thickness of the high melting point metal paste is preferably 10 to 30 μm. If the printing thickness is less than 10 μm, the thickness of the active metal brazing material layer will vary, reducing the bonding strength. On the other hand, if it exceeds 30 μm, no further effect will be obtained. The high melting point metal paste is printed in a uniform thickness on the end surface of the ceramic component by a screen printing method or the like. If the printing thickness is not uniform, a difference in bonding strength will occur between the thick and thin parts. For this reason, it is preferable that the difference in printing thickness between the thick and thin parts is 5 μm or less.
[0044] The high melting point metal paste printed on the ceramic parts is dried in the air or the like. If the drying temperature is low and the drying time is short, the solution components of the paste are not sufficiently volatilized, and voids may occur during bonding. Conversely, if the drying temperature is high and the drying time is long, oxidation of the surface of the high melting point metal paste may progress, and the bonding temperature may change. For this reason, the drying temperature is 50 to 100°C, preferably 60 to 80°C. The drying time is 5 to 30 minutes, preferably 10 to 20 minutes.
[0045] After drying the high melting point metal paste, the metallization layer is formed by heating in a wet hydrogen nitrogen atmosphere. The heating temperature is 1350 to 1550°C. In the high melting point metal method, a glass phase diffuses from the ceramic parts to form a strong bonding layer. If the heating temperature is lower than 1350°C, the diffusion of the glass phase is insufficient and the bonding strength may decrease. Conversely, if the heating temperature is higher than 1550°C, the glass phase may reach the surface of the metallization layer and reduce the adhesion strength with the plating described below. A continuous furnace or batch furnace is used for heating. A continuous furnace is superior in terms of mass production.
[0046] The metallized layer formed by the high melting point metal is plated to improve the bonding with the brazing material. There are various types of plating, such as nickel plating and gold plating, but nickel plating has excellent corrosion resistance and excellent cost performance. Nickel plating is classified into electrolytic nickel plating, which is performed by passing an electric current, and electroless nickel plating, which is not performed by passing an electric current. Electrolytic nickel plating has a lower cost of chemicals than electroless nickel plating and has excellent cost performance. It is preferable to perform electrolytic nickel plating with a thickness of 1 to 3 μm on the metallized layer. If the thickness is thinner than 1 μm, the wettability of the brazing material described below may decrease. If the thickness is thicker than 3 μm, it is too thick to ensure the wettability of the brazing material, and if it is too thick, there is a possibility of blistering defects occurring.
[0047] The formed plating is joined to the metal parts. A brazing material is used for the joining. As a brazing material, silver brazing is preferred because it wets easily with nickel plating and bonds firmly to metal parts. Silver brazing (BAg-8) made of 72% silver and 28% copper is often used to join ceramics and metal parts. BAg-8 according to "Silver Brazing (JIS Z3261:1998)" contains 71-73% silver (Ag), 27-29% copper (Cu), and a total of 0.15% or less of other elements. BAg-8 does not contain evaporated metals, so it is suitable for brazing electronic tubes and vacuum tubes, and is preferable because it has excellent electrical conductivity due to its high silver content and can be used for parts that have a high melting temperature and can withstand high temperatures. Silver brazing is processed into a sheet or wire ring shape and placed between the plating surface and the metal part, or made into a paste and printed on the plating surface or the surface of the metal part. The joining temperature of silver brazing is 650-900°C, preferably 750-820°C. If the joining temperature is too low, the silver brazing material may not melt sufficiently and the joint may not be completed. Conversely, if the joining temperature is too high, the silver brazing material may melt too much and spread, causing solder breaks and voids.
[0048] Furthermore, the silver brazing joining atmosphere is a non-oxidizing atmosphere as necessary. Examples of non-oxidizing atmospheres include a nitrogen atmosphere and a hydrogen nitrogen atmosphere. By using a non-oxidizing atmosphere, oxidation of the joining layer can be suppressed, and the joining strength can be improved. A continuous furnace or a batch furnace is used for silver brazing. A continuous furnace is superior in terms of mass production, while a batch furnace allows easy control of the temperature and atmosphere. Silver brazing is performed by heating the parts in the above atmosphere for a specified period of time.
[0049] According to the method for manufacturing a ceramic sealed component in the embodiment of the present invention, a ceramic sealed component excellent in cost performance can be obtained while maintaining the airtightness of the sealed component.
[0050] (Examples 1 to 12, Comparative Examples 1 to 8 ) Alumina with manganese oxide (MnO2), two Auxiliaries such as silicon oxide (silica: SiO2) and magnesium oxide (magnesia: MgO) were added to prepare granulated powder with a composition of 92% alumina by mass. The granulated powder was molded in a die press and sintered in air at 1500°C to obtain a cylindrical ceramic part with an outer diameter of 50 mm, inner diameter of 38 mm, height of 50 mm, outer diameter C chamfer of 0.5 mm, and inner diameter C chamfer of 0.5 mm. In addition, Arsil (zirconia-added alumina) was made by adding zirconia to alumina to obtain 80% alumina by mass, molding it in the same way as alumina, and sintering it in air at 1500°C to obtain a cylindrical part with the same dimensions as the alumina part. In addition, silicon nitride was mixed with silica (S iO A cylindrical silicon nitride part with the same dimensions as the alumina part was obtained by adding 1 mass% of 2), 3 mass% of yttria (yttrium oxide: Y2O3), and 1 mass% of alumina as auxiliary agents, molding in the same manner, and sintering in nitrogen at 1800°C. Also, a cylindrical aluminum nitride part with the same dimensions as the alumina part was obtained by adding 3 mass% of yttria as auxiliary agent to aluminum nitride (AlN), molding in the same manner, and sintering in nitrogen at 1800°C.
[0051] The ceramic parts obtained by sintering were barrel polished to remove dust and other debris, and one end face was then roughened by blasting. The arithmetic mean surface height (Sa) of both end faces of the ceramic parts was then measured using a Keyence laser microscope (VK-X3000). The measurement conditions were as follows: 1. Measure the diameter of the ceramic parts by measuring 44 mm in diameter from the center of the width of the ceramic parts (diameter 44 mm). 2 A range of .5 mm was measured. The number of measurements was three, and the measured value was the average of the three. The measurement results of the arithmetic mean surface height of the face are shown in Table 1. In the embodiment, the end face with the increased arithmetic mean surface height of the face was designated S1, and the end face without processing was designated S2. In contrast, in Comparative Examples 1 and 6, neither end face was processed by blasting. In the other comparative examples, the end face with the increased arithmetic mean surface height of the face in the embodiment was designated S2, and the end face without processing in the embodiment was designated S1. In Table 1, ceramics that were processed in the same way were configured as the same lot. For example, Examples 1 to 6, 10 to 12 and Comparative Examples 3 and 8 are lots configured of ceramic parts that were manufactured and processed in the same way and had their arithmetic mean surface heights measured. In Table 1, aluminum nitride parts are written as AlN.
[0052] Next, the method of joining the ceramic parts and the metal parts was selected from the active metal joining method and the high melting point metal method. In the examples and comparative examples in which the active metal joining method was selected, the metal powder compounding ratio was copper powder, tin powder, and titanium hydride (TiH) powder. quality The mixture was mixed to a ratio of 60:30:10 by volume, and ethyl cellulose and terpineol were added to make a paste using a kneader to produce an active metal brazing paste. A 60 μm thick active metal paste was printed on the upper and lower ends (ring parts) of the ceramic parts by screen printing using a 100 mesh screen with an outer diameter of 48 mm and an inner diameter of 40 mm, and dried at 100°C in air. Next, using the metal parts described below, the metal parts, ceramic parts, and metal parts were set in a jig in this order, and heated in a vacuum atmosphere at 820°C or higher for 10 minutes to bond the metal parts and ceramic parts to produce a ceramic sealed part.
[0053] In the examples and comparative examples in which the high melting point metal method was selected, the metal powder blend ratio was molybdenum (Mo) powder and manganese (Mn) powder. quality The mixture was mixed to a ratio of 90:10 by volume, and ethyl cellulose and terpineol were added to the mixture and the mixture was made into a paste by a kneader to produce a high melting point metal paste. A 100 mesh screen with an outer diameter of 48 mm and an inner diameter of 40 mm was used to screen print a 25 μm thick high melting point metal paste on the upper and lower ends (ring parts) of the ceramic parts, and the paste was dried at 100°C in air. Next, a metallized layer of high melting point metal was formed on the surface of the ceramic parts by heating at 1450°C or higher for 30 minutes in a wet hydrogen nitrogen atmosphere. Next, a nickel layer with a thickness of 2 μm was formed on the surface of the metallized layer by electrolytic nickel plating. Next, the metal parts, silver solder, ceramic parts, silver solder, and metal parts were set in a jig in this order using 0.1 mm thick silver solder (BAg-8), and the metal parts and ceramic parts were joined by heating at 820°C or higher for 10 minutes in a hydrogen nitrogen atmosphere continuous furnace to produce a ceramic sealed part.
[0054] (Table 1) TIFF0007635345000002.tif101100
[0055] In addition, a copper plate measuring 10 mm x 100 mm x 0.5 mm was prepared instead of a metal part for measuring the bonding strength. In the active metal method, the copper plate and the ceramic part printed with an active metal layer were set in a jig in that order and bonded by heating to prepare a test sample for the bonding strength. In the high melting point metal method, copper plate The ceramic part was placed in the order of the solder, the silver solder, and the plated layer on the metallized layer, and heated to prepare a test sample for the bonding strength. The ceramic part was fixed to a tensile strength tester and bent vertically. copper plate The adhesive strength (peel strength) was measured by pulling the adhesive upward at 5 mm / min.
[0056] The measurement results of the peel strength are shown in Table 2. In Table 2, Examples 1, and 7 to 10 are shown as representatives of the same lot. In addition, the peel strength of the S1 and S2 surfaces was measured using different ceramic parts from the same production lot, but for convenience, they are listed in the same row in Table 2.
[0057] (Table 2) TIFF0007635345000003.tif33111
[0058] As can be seen from Table 2, the peel strength of the surface where the arithmetic mean surface height of the surface was increased (surface height S1) was greater than that of the surface where the arithmetic mean surface height was not increased (surface height S2). This is because by increasing the arithmetic mean surface height of the surface, the bonding area is increased and physical bonding is performed through the anchor effect, etc., resulting in greater bonding strength.
[0059] Table 3 shows the metal A parts and metal B parts used in the examples and comparative examples. The materials of the metal A parts are iron and iron alloys, such as pure iron (Fe), carbon steel (S45C), stainless steel (SUS304, SUS430), Kovar, and 42 alloy. The materials of the metal B parts are copper and copper alloys, such as oxygen-free copper and phosphorus-deoxidized copper. These metal parts were machined into a cylindrical shape with a height of 20 mm, an outer diameter of 48 mm, an inner diameter of 46 mm, and an inner diameter of 40 mm, with the tip of the joining side machined inward at a substantially right angle. In the examples and comparative examples, the combinations of metal parts shown in Table 3 were used. The surfaces of the machined iron and iron alloy parts were plated with 2 μm of nickel.
[0060] Next, the upper part of the ceramic sealed part was applied with silicone and held down with a circular jig made of Viton rubber, and the lower part was fixed to a helium leak detector and sucked in to perform a helium leak test. The helium leak test was performed in accordance with the vacuum spray method (spray method) of the "Helium Leak Test Method" (JIS Z2331:2006), and the helium leak rate was 1×10 at a vacuum of 1.3 μPa. -9 Pa·m 3If no leak of 1 / s or more occurred, the test was deemed to have passed, and if a leak occurred, the test was deemed to have failed, and the number of defective products was calculated.
[0061] Furthermore, a thermal shock test (TST) was conducted on the ceramic sealed parts that had passed the helium leak test. The test conditions were low temperature condition -40°C x 30 minutes, high temperature condition 125°C x 30 minutes, and a transfer time of 10 seconds or less for a total of 20 test cycles. After the thermal shock test, a helium leak test was conducted in the same manner as before the test. The number of defective parts was calculated by regarding no leakage as passing and leakage as failing. The test results for the examples and comparative examples are shown in Table 3.
[0062] (Table 3) TIFF0007635345000004.tif11196
[0063] The ceramic sealed parts according to the embodiment and comparative example 2 had a desirable range of leak defects in the helium leak test. This is because the joint strength obtained by combining the ceramic part and the metal part was appropriate, and the joint configuration was such that it would not break due to stress generated by the difference in thermal expansion during joining. In contrast, the comparative example had a large number of leak defects. This was because the joint strength was not high enough, and the difference in thermal expansion between the ceramic part and the metal part caused damage to the joint, making it impossible to maintain airtightness.
[0064] In addition, the ceramic sealed parts according to the examples did not have any leak failures or only a small amount of leaks in the helium leak test after the TST. This is because the joint strength obtained by combining the ceramic parts and the metal parts was appropriate, and the joint configuration was such that it would not break due to the stress generated by the difference in thermal expansion under the TST test conditions. In contrast, in the comparative example, a helium leak failure occurred after the TST. This is because the joint strength obtained by combining the ceramic parts and the metal parts was insufficient. Even if the joint strength was sufficient, the damage caused by increasing the surface roughness of the ceramic parts was so great that it led to the destruction of the ceramic parts, creating a leak path.
[0065] As is clear from the results shown above, the Examples showed improvements in leak characteristics and reliability in TST compared to the Comparative Examples.
[0066] Although several embodiments of the present invention have been illustrated above, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, modifications, etc. can be made without departing from the gist of the invention. These embodiments and their modifications are included in the scope and gist of the invention, and are included in the scope of the invention and its equivalents described in the claims. In addition, the above-mentioned embodiments can be implemented in combination with each other. [Explanation of symbols]
[0067] 1...Ceramics sealing parts 2. Ceramic parts 21, 22...end face 3…Metal A part 4…Metal B parts 5...Joining layer 6...Active metal brazing layer 7…Metallized layer 8…Plating layer 9…Brazing layer
Claims
1. A ceramic sealed part in which two metal parts made of different materials are joined to the end faces of a ceramic part, When the arithmetic mean surface height of one end face of the ceramic part is S1 and the arithmetic mean surface height of the other end face is S2, S1 / S2≧1.2, A ceramic sealed component, characterized in that a metal part made of iron, an iron alloy, or an iron-nickel alloy is joined via a joining layer to an end face having an arithmetic mean surface height S1.
2. 2. The ceramics sealed part according to claim 1, wherein a metal part made of copper or a copper alloy is joined via a joining layer to an end face of the ceramics part having an arithmetic mean surface height S2.
3. A ceramic sealed part as described in claim 1 or claim 2, characterized in that the bonding layer of the ceramic sealed part described in claim 1 or claim 2 is a bonding layer comprising a metallized layer made of one or more high melting point metals selected from tungsten and molybdenum formed on the surface of the ceramic part, a nickel plating layer formed on the surface of the metallized layer, and a solder material containing copper and silver on the surface of the nickel plating layer.
4. 4. The ceramics sealing part according to claim 3, wherein the ceramics part is made of aluminum oxide.
5. A ceramic sealed part as described in claim 1 or claim 2, characterized in that the bonding layer of the ceramic sealed part as described in claim 1 or claim 2 is a bonding layer consisting of one or more active metals selected from titanium, zirconium and hafnium, and one or more brazing metals selected from copper and silver.
6. 6. The ceramics sealing part according to claim 5, wherein the ceramic part of the ceramics sealing part according to claim 5 is one selected from the group consisting of aluminum oxide, silicon nitride and aluminum nitride.
7. A method for manufacturing a ceramic sealed part in which two metal parts made of different materials are joined to the end faces of a ceramic part, comprising: A step of preparing a ceramic part of the ceramic sealing component according to claim 1; a step of joining the ceramic part and the metal part with one or more active metals selected from titanium, zirconium, and hafnium, and one or more brazing metals selected from copper and silver; Equipped with The method for manufacturing a ceramic sealed part is characterized in that the metal part to be joined to the end face having an arithmetic mean surface height S1 of the ceramic part is made of iron, an iron alloy, or an iron-nickel alloy.
8. A method for manufacturing a ceramic sealed part in which two metal parts made of different materials are joined to the end faces of a ceramic part, comprising: A step of preparing a ceramic part of the ceramic sealing component according to claim 1; forming a metallized layer made of a high melting point metal on an end surface of the ceramic component; forming a nickel plating on the surface of the metallization layer; The method includes a step of joining the nickel plating and a metal part with a brazing material containing copper and silver, The method for manufacturing a ceramic sealed part is characterized in that the metal part to be joined to the end face having an arithmetic mean surface height S1 of the ceramic part is made of iron, an iron alloy, or an iron-nickel alloy.
9. A method for manufacturing a ceramic sealed part in which two metal parts made of different materials are joined to the end faces of a ceramic part, comprising:
9. The method for manufacturing a ceramics sealed part according to claim 7 or 8, characterized in that copper or a copper alloy is bonded via a bonding layer to an end face of the ceramics sealed part according to claim 1, the end face having an arithmetic mean surface height S2 of the ceramics part.
10. A method for manufacturing a ceramic sealed part in which two metal parts made of different materials are joined to the end faces of a ceramic part, comprising:
10. The method for producing a ceramics sealed part according to claim 9, wherein the ceramic part of the ceramics sealed part according to claim 1 is one selected from the group consisting of aluminum oxide, silicon nitride and aluminum nitride.
Citation Information
Patent Citations
Semiconductor device
JP1989046978A
Metal-ceramic bonded material and method for producing the same
JP2001220253A
Bonding structure and semiconductor element storing package
JP2010245141A
Ceramic substrate, ceramic circuit board, and method of manufacturing ceramic substrate
JP2023050453A
Ceramic-metal bonded body, method for manufacturing the bonded body and semiconductor device using the bonded body
WO2008004552A1